2023
DOI: 10.3390/biomimetics8050447
|View full text |Cite
|
Sign up to set email alerts
|

New Glycosalen–Manganese(III) Complexes and RCA120 Hybrid Systems as Superoxide Dismutase/Catalase Mimetics

Valeria Lanza,
Graziella Vecchio

Abstract: Reactive oxygen species are implicated in several human diseases, including neurodegenerative disorders, cardiovascular dysfunction, inflammation, hereditary diseases, and ageing. MnIII–salen complexes are superoxide dismutase (SOD) and catalase (CAT) mimetics, which have shown beneficial effects in various models for oxidative stress. These properties make them well-suited as potential therapeutic agents for oxidative stress diseases. Here, we report the synthesis of the novel glycoconjugates of salen complex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 62 publications
(91 reference statements)
0
2
0
Order By: Relevance
“…In an in vivo experiment, EUK-8 significantly reduced the phosphorylation level of several inflammatory proteins such as p38 member of MAPK pathway, protein kinase B (Akt), and transcription factor p65, and inhibited pro-inflammatory cytokine interleukin-6 and chemokine CXCL1 ( Jayachandra et al, 2023 ). A recent study reported a synthesis of new glycosalen-Mn(III) complexes of EUK-108 with glucose and galactose ( Lanza and Vecchio, 2023 ). These complexes showed both SOD- and CAT-like activities and could be advantageous for future clinical applications.…”
Section: Antioxidants That Potentially Can Be Used For the Developmen...mentioning
confidence: 99%
“…In an in vivo experiment, EUK-8 significantly reduced the phosphorylation level of several inflammatory proteins such as p38 member of MAPK pathway, protein kinase B (Akt), and transcription factor p65, and inhibited pro-inflammatory cytokine interleukin-6 and chemokine CXCL1 ( Jayachandra et al, 2023 ). A recent study reported a synthesis of new glycosalen-Mn(III) complexes of EUK-108 with glucose and galactose ( Lanza and Vecchio, 2023 ). These complexes showed both SOD- and CAT-like activities and could be advantageous for future clinical applications.…”
Section: Antioxidants That Potentially Can Be Used For the Developmen...mentioning
confidence: 99%
“…Manganosalen complexes are a class of synthetic catalysts with antioxidant capacity [ 1 , 2 , 3 , 4 , 5 ]. Their design is inspired by natural enzymes such as catalases, superoxide dismutases, or glutathione peroxidases, which are all part of the body’s antioxidant barrier that controls the excess of reactive oxygen species (ROS) [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%